Acoustic vibration-induced stress dynamics in high viscosity non-Newtonian fluids within a wedge flow channel - Binwu Wu; Xiaobin Zhan; Lei Yu; Binhuan Ye (Chemical Engineering Journal Advances, 2025)
Acoustic vibration is a new technology for improving the mixing of high viscosity non-Newtonian fluids, while the study of the distribution of stress and dynamic evolution of its mixing process is an important prerequisite to improve the efficiency and ensure safety. This study investigates the stress characteristics of high viscosity, shear thinning non-Newtonian fluids in a wedge flow channel under acoustic vibration using CFD. The individual and combined effects of amplitude and frequency on the mixing process are examined. As a result, high fill rate is observed at low vibration intensities, but the fill rate decreases as the intensity increases. The spatial distribution of compressive and shear stresses is strongly correlated with the fill rate. As the vibration intensity increases, the compressive stress follows an ''increase – decrease – increase'' trend, while the shear stress follows a ''stable–increase'' trend, both becoming less periodic and more fluctuating. Under the same acceleration, the combination of low frequency and high amplitude vibration (46∼50 Hz, 6∼7 mm) is more effective in achieving full-field dispersion in the liquid phase, reducing compressive stress without excessively increasing shear stress.